Neurological Manifestations of Dengue Infection - Li, Guo-Hong; Ning, Zhi-Jie; Liu, Yi-Ming; Li, Xiao-Hong (Frontiers in Cellular and Infection Microbiology, 2017)
Dengue counts among the most commonly encountered arboviral diseases, representing the fastest spreading tropical illness in the world. It is prevalent in 128 countries, and each year >2.5 billion people are at risk of dengue virus infection worldwide. Neurological signs of dengue infection are increasingly reported. In this review, the main neurological complications of dengue virus infection, such as central nervous system (CNS), peripheral nervous system, and ophthalmic complications were discussed according to clinical features, treatment and possible pathogenesis. In addition, neurological complications in children were assessed due to their atypical clinical features. Finally, dengue infection and Japanese encephalitis were compared for pathogenesis and main clinical manifestations.